Adherence to Iron and Folic Acid Supplementation and its determinants among pregnant women in East Africa: Analysis of Demographic and Health Surveys data from nine East African countries - Alemu, Nanati Legese; Roba, Kedir Teji; Getaneh, Henok Demeke; Raru, Temam Beshir; Daba, Alemneh Kabeta; Worku, Netsanet; Abebe, Zeweter (PLOS ONE, 2025)
Introduction Anemia due to deficiency of nutrients like iron and folic acid (IFA) is one of the global public health issues that has contributed to an unacceptably high proportion of maternal and childhood morbidity and mortality. IFA supplementation (IFAS) during pregnancy is critical for reducing anemia and related undesired outcomes. However, comprehensive evidence on the magnitude of adherence to IFA supplementation and its associated factors in East Africa remains limited. Objective The objective of this study was to assess the level of adherence to IFAS during pregnancy and to identify the factors associated with adherence among pregnant women in East African countries. Methods In this study, we analyzed demographic and health survey (DHS) data from nine countries in East Africa, yielding a sample of 57,283 pregnant women. The study used multilevel mixed effects cross-sectional design. We applied four models, and we compared the models using the Akaike information criterion (AIC) and the Bayes information criterion (BIC). The model with smaller AIC and BIC was the best to fit the data, and the interpretation of the fixed effects was based on this model. To measure cluster variation, we used the intra-cluster correlation coefficient (ICC) standard deviation. Finally, we utilized fixed effects to estimate the association between adherence to IFAS and the independent variables, and we reported the results as an odds ratio with a 95% confidence range. Results The overall prevalence of adherence to IFAS among pregnant women in East Africa was 35.8% (95% CI: 35.4–36.2). This prevalence ranges from 3.8% in Burundi to 83.7% in Zambia, with significant differences between countries. Adherence to IFAS among women with secondary and more than secondary level of education was higher by 29% (AOR = 1.29, 95% CI: 1.19, 1.41) and 92% (AOR = 1.92, 95% CI: 1.68, 2.20), respectively, compared to women with no formal education. Adherence to IFAS among women who had the first ANC visit on the second and third trimesters was lower by 16% (AOR = 0.84, 95% CI: 0.80, 0.89) and 74% (AOR = 0.26, 95% CI: 0.23, 0.30), respectively, compared to those with the first ANC visit on the first trimester. Furthermore, four or more ANC visits during pregnancy and a lower distance to health facilities were significantly associated with adherence to IFAS in East Africa. Conclusions Only one-third of pregnant women in East Africa adhered to IFAS. Adherence was significantly associated with higher education, early ANC booking, more frequent ANC visits, proximity to health facilities, and country of residence. Interventions should prioritize improving women’s education, promoting timely and frequent ANC attendance, and addressing country-specific barriers to improve IFAS uptake and maternal outcomes.